The Influence of Social Media and Perceived Barriers on Formation of Social Entrepreneurial Intention: A Conceptual Framework - Osama, Al Jameel; Adam, Sabrinah (Business Management and Strategy, 2024)
Social entrepreneurship is garnering global attention and emerging as a noteworthy business model. Scholars and practitioners assert that social entrepreneurship is pivotal in addressing and resolving social problems through sustainable solutions. However, evidence suggests that barriers can impede individuals from becoming social entrepreneurs or postpone the decision to initiate a social venture. Furthermore, despite the influential role of social media in shaping general public attitudes and behavior, there is limited attention given to its impact on social entrepreneurship. Consequently, this study employs the theory of planned behavior to create a new framework that incorporates various variables potentially influencing social entrepreneurial intention (SEI). This study contributes to the social entrepreneurship literature by offering new insights into the factors affecting SEI. Beyond advancing theoretical knowledge, it enhances policymakers’ understanding of the antecedents of SEI, enabling them to formulate effective policies that encourage suitable individuals to pursue social entrepreneurship.